Preceptors' experiences in guiding nursing students to use research findings and to implement evidence-based practice† - Ligita Titan; Nurbianti Suma; Yulanda Nita Arisanti; Pramana Yoga; Saputri Cindiarty Kurnia; Kumala Eka Ersa Mayang (Sciendo, 2024)
Evidence-based practices (EBPs) have been taught to students by identifying the best evidence/evidence from research results. However, the experiences of Indonesian nurse preceptors in helping students implement research findings have not been explored thoroughly. This study aimed to explore Indonesian nurse preceptors in guiding nursing students to use research findings.